2018
DOI: 10.1007/s10792-018-1018-8
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of propranolol in very preterm infants at the risk of retinopathy of prematurity: Which newborn and when?

Abstract: When given in the neovascularization phase of the ROP, propranolol was found to be effective in the stage 2 (advanced stage) ROP patients but in stage 0-1 (early-stage) ROP patients, its efficacy was not sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The difference among the studies can be a result of the difference among the number of the subjects that have had a need for more aggressive actions. 14,15 In this study, the only side effect has been one case of hypoglycemia in the third day of the cure (Bs = 35) in which the patient showed no sign of the hypoglycemia but he was let out of the study. In other similar studies including Makhoul and Aldo Bancalari studies, no side effects were seen.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The difference among the studies can be a result of the difference among the number of the subjects that have had a need for more aggressive actions. 14,15 In this study, the only side effect has been one case of hypoglycemia in the third day of the cure (Bs = 35) in which the patient showed no sign of the hypoglycemia but he was let out of the study. In other similar studies including Makhoul and Aldo Bancalari studies, no side effects were seen.…”
Section: Discussionmentioning
confidence: 78%
“…The change of the retinopathy and the ocular areas of the disease in each study can be a reason for this, too. [11][12][13][14][15] Because of the patient's need for drug discontinuation and more aggressive therapies, drug consumption duration is different. In this study, the difference of the drug consumption duration between the group that has shown reactions to the cure and the group without reactions has shown significant, while in Ozturk MA study, the drug consumption duration has been a variable and there has not been a significant relation between the two groups, unlike our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Korkmaz et al demonstrated that the administration of propranolol in patients with stage 2 retinopathy significantly reduced the need for laser therapy, but there was no difference in the higher stages of retinopathy (25). Meanwhile, Ozturk and Korkmaz reported that propranolol administration in neonates with stage 2 retinopathy was effective in preventing progression to higher levels although it was not effective in reducing the risk of ROP in stages 0 and 1 (26). Based on the results of Bührer et al, the prophylaxis administration of propranolol did not lead to any difference in the risk of developing ROP in the neonates of the intervention group (27).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these preclinical studies, the efficacy and the safety of a treatment with propranolol, administered during the proliferative phase, was tested in human preterm newborns with ROP in a series of pilot clinical trials (Filippi et al, 2013;Makhoul et al, 2013;Bancalari et al, 2016;Korkmaz et al, 2017;Sanghvi et al, 2017;Sun et al, 2018;Ozturk and Korkmaz, 2019). Three recent meta-analyses demonstrated that oral administration of propranolol to newborns with ROP slows down the progression of retinal neovascularization and reduces the indication for laser photocoagulation or anti-VEGF drugs (Kaempfen et al, 2018;Stritzke al., 2019;Kong et al, 2021).…”
Section: Treatment With Propranololmentioning
confidence: 99%